Immunity Debt for Seasonal Influenza After the COVID‐19 Pandemic and as a Result of Nonpharmaceutical Interventions: An Ecological Analysis and Cohort Study - Li Chen; Yuchen Guo; Kim López‐Güell; Jun Ma; Yanhui Dong; Junqing Xie; Daniel Prieto Alhambra (Advanced Science)
Abstract Non‐pharmaceutical interventions (NPIs) during the COVID‐19 pandemic significantly reduced influenza transmission. This study explores the hypothesis of “immunity debt” which suggests increased vulnerability to influenza following reduced exposure during the pandemic. World Health Organization aggregated data on influenza from 116 countries and its association with NPI intensity as measured by the COVID‐19 Stringency Index is analyzed. Where individual‐level data available (France, the United Kingdom, Spain, Italy, Belgium, and Romania), the analyses of influenza monthly rates in six European countries (France, the United Kingdom, Spain, Italy, Belgium, and Romania) are replicated. The results indicate globally a 46.3% (95% CI: 15.79–70.78%) reduction in influenza cases during COVID‐19 restrictions in the winter season, followed by a 131.7% (95% CI: 34.95–255.78%) increase in the first postrelaxation winter and a 161.2% (95% CI: 31.88–382.16%) increase in the summer as compared to the predicted level based on historical influenza epidemic trends. In addition, a positive association between the Stringency Index and post‐relaxation influenza surge is observed globally (R2 = 0.14–0.17) and replicated regionally. The findings support the population immunity debt hypothesis for influenza and call for proactive preparations against its consequences in future pandemics.